Analysis of tidal amplitude changes using the EMD method. (15th September 2017) - Cheng, Yongcun; Ezer, Tal; Atkinson, Larry P.; Xu, Qing
Abstract: Empirical Mode Decomposition (EMD) analysis of sea level data has been used in the past mostly to study long-term sea level rise (SLR) and decadal/multidecadal variations. However, application of EMD to high-frequency sea level variability is rare, so here EMD is tested as a tool to analyze hourly sea level data and detect time-dependent changes in tidal characteristics. Traditional Harmonic Analysis (HA) cannot deal with non-linear, non-stationary processes such as storm surges. Here, the two methods are compared in the analysis of 17 tide gauge records from the U.S. East Coast, demonstrating considerable trends and interannual variability in the semidiurnal tides. The time dependent changes of tidal characteristics are unique for each region and in some cases for specific locations. The results show that in most stations the highest and second-highest frequency modes of the EMD can capture the semidiurnal and diurnal tides, respectively. High correlation is often found between the variations of the first EMD mode and the amplitude of the M2 tide obtained from HA. However, in some locations the high frequency EMD mode captures other (non M2 ) variability and in other locations a sudden shift in tidal characteristics is found. In Baltimore for example, during the 1970s the amplitude suddenly increased for the M2 tide but decreased for the S2 tide, and in Wilmington a significant increase ( 20 cm in 80 years) in the amplitude of the M2 tide is detected by both methods. These changes could indicate an instrumental change or a morphological change due to storm surges. This short report is meant to demonstrate a new tidal analysis tool that can help studies of changes in tidal characteristics and the relation of these changes to morphology change, sea level rise and climate change. Highlights: Coherent tidal amplitude changes captured by the EMD analysis and Harmonic Analysis method. Non-stationary method EMD that can detect changes in tidal characteristics over time with one calculation of an entire record. The highest frequency mode of EMD analyzed hourly tide gauge data denote the variations of semidiurnal tide.